The Philippine cookbook - De Guzman, Virginia Roces (Makati City, Philippines : Bookmark, 2000)
This book is a compilation of such recipes. Family and dear friends have generously shared a wealth of culinary gems which have little variations featured here, those extra touches and twists, that make this book different.